Magnetic-ordered and superconducting units inside surface layers of PbTe:Eu crystals grown from melt by using the Bridgman method - Zayachuk, D.M.; Ilyina, O.S.; Kaczorowski, D.; Mikityuk, V.I.; Shlemkevych, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Presented in this work are the results of the first systematic study of magnetic properties inherent to surface layers of PbTe:Eu crystals grown from melt with a low initial concentration of Eu impurity using the Bridgman method. The magnetic field dependences of magnetization at the temperature 1.72 K and temperature dependences of magnetic susceptibility within the temperature range 1.7 to 10 K of the surface powder samples has been investigated. Inside the surface layers, formation of both small magnetic complexes based on Eu impurity and lead-based inclusions superconducting at low temperatures, which originate in a correlated way during the growth process of doped ingots, has been established. The observed correlations are manifested in a consistent distribution of both europium-based and leadbased units along the lateral surface, where the probability of their formation increases towards the end of the doped ingot. Based on the analysis of the obtained magnetic data, it has been suggested that the lead-based inclusions, being formed within the surface layer of PbTe:Eu crystals during the process of their growth and passing into a superconducting state on cooling, are the type II superconductors with a very high top critical field Hc₂ at low temperatures. At T = 1.7 K, Hc₂ of the inclusions is estimated to exceed 50.0 kOe. The important role of the background oxygen impurity in format Remove selected